Challenges and strategies in conducting sexual and reproductive health research among Rohingya refugees in Cox’s Bazar, Bangladesh - Ahmed, Rushdia; Aktar, Bachera; Farnaz, Nadia; Ray, Pushpita; Awal, Abdul; Hassan, Raafat; Shafique, Sharid Bin; Hasan, Md Tanvir; Quayyum, Zahidul; Jafarovna, Mohira Babaeva; Kobeissi, Loulou Hassan; El Tahir, Khalid; et al. (Conflict and health, 2020)
Background Rohingya diaspora or Forcibly Displaced Myanmar Nationals (FDMNs), took shelter in the refugee camps of Cox’s Bazar, Bangladesh due to armed conflict in the Rakhine state of Myanmar. In such humanitarian crises, delivering sexual and reproductive health (SRH) services is critical for better health outcomes of this most-at-risk population where more than half are adolescent girls and women. This is a reflective paper on challenges and related mitigation strategies to conduct SRH research among FDMNs. The research on which this paper is based employed a concurrent mixed-method design combining a cross-sectional survey and qualitative interviews and group discussions with FDMNs to understand their SRH needs and demand-side barriers. Assessment of health facilities and qualitative interviews with healthcare providers and key stakeholders were carried out to assess facility readiness and supply-side barriers. Challenges and strategies The researchers faced different challenges while conducting this study due to the unique characteristics of the FDMN population and the location of the refugee camps. The three key challenges researchers encountered include: sensitivity regarding SRH in the FDMNs, identifying appropriate sampling strategies, and community trust issues. The key approaches to overcome these challenges involved: actively engaging community members and gatekeepers in the data collection process to access respondents, identifying sensitive SRH issues through survey and exploring in-depth during qualitative interviews; and contextually modifying the sampling strategy. Conclusion Contextual adaptation of research methods and involving community and local key stakeholders in data collection are the key lessons learnt from this study. Another important lesson was researchers’ identity and positionality as a member of the host country may create distrust and suspicion among the refugees. The multi-level complexities of humanitarian settings may introduce unforeseen challenges and interrupt research plans at different stages of research which require timely and contextual adaptations.